2014
DOI: 10.1002/jsid.246
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing and evaluating new automotive HMI image enhancement algorithms under bright light conditions using display reflectance characteristics

Abstract: -We have developed and investigated new image enhancement (tone mapping) algorithms for automotive Human Machine Interfaces (HMIs) so that displays can be better read in bright light. Our 'ΔL/L' approach with adaptive color rendering (CR) is based on Weber's fraction and is easy to use with various displays and illumination variables. In tests with automotive HMIs under different lighting conditions -including driver glare-the 'ΔL/L + CR' image enhancement method proved to be a good choice. First, reflective, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…1 demonstrates how the display appears to the driver in 2 lux and 21K lux (first row) and how using our application in dark and bright conditions can clarify important details presented on the screen. DRIVEvue dark and bright modes use similar algorithms but consider the differences between human contrast sensitivity and color perception in dark 5,7,8 and bright 2, 3, 4 environments. This approach consists of three major algorithms: global contrast retargeting, local contrast retargeting, and color retargeting 5 .…”
Section: Drivevuementioning
confidence: 99%
“…1 demonstrates how the display appears to the driver in 2 lux and 21K lux (first row) and how using our application in dark and bright conditions can clarify important details presented on the screen. DRIVEvue dark and bright modes use similar algorithms but consider the differences between human contrast sensitivity and color perception in dark 5,7,8 and bright 2, 3, 4 environments. This approach consists of three major algorithms: global contrast retargeting, local contrast retargeting, and color retargeting 5 .…”
Section: Drivevuementioning
confidence: 99%
“…A study has shown that visual performance of displays can be improved when the luminance or contrast ratio becomes higher [8]. In addition, there are studies on the image quality due to the reflection of the glass of the LCD top plate along with the ambient illuminance [9,10]. However, a dynamic visual information processing task of LCD and OLED display can induce visual fatigue and both temporal and environmental factors affected visual load [11].…”
Section: Introductionmentioning
confidence: 99%
“…In today's world, every individual spends a lot of time in front of displays in various applications such as consumer electronic devices (e.g. smart phones, tablets and laptops), automotive industry [3], and virtual reality interfaces (e.g. head-mounted displays).…”
Section: Introductionmentioning
confidence: 99%